2005
DOI: 10.1007/s10557-005-6892-4
|View full text |Cite
|
Sign up to set email alerts
|

Glucagon Like Peptide-1 is Protective Against Myocardial Ischemia/Reperfusion Injury when Given Either as a Preconditioning Mimetic or at Reperfusion in an Isolated Rat Heart Model

Abstract: A number of recent studies have identified potential beneficial effects for Glucagon Like Peptide-1 (GLP-1), a potent gut incretin hormone with notable cell regulatory and anti-apoptotic actions predominantly in the pancreas [1]. However, recent studies have not only identified receptors for GLP-1 in the myocardium [2] but also demonstrated its beneficial roles in cardiac physiology and metabolism. Investigators reported improved left ventricular performance and reduced stunning in both clinical and experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
71
1
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(80 citation statements)
references
References 10 publications
7
71
1
1
Order By: Relevance
“…Although evidence from multiple studies suggests that GLP-1 has important cardiovascular actions, 12,14,15,38,39 the mechanisms underlying these diverse effects have not been fully elucidated. Our results propose a novel 2-pathway schema for cardiovascular actions of GLP-1, one that depends on the GLP-1R for inotropic action, glucose uptake, ischemic preconditioning, and mild vasodilatory actions and the second that depends on rapid metabolism of GLP-1 to GLP-1 , the latter having GLP-1R-independent effects on postischemic recovery of cardiac function and vasodilation.…”
Section: Discussionmentioning
confidence: 99%
“…Although evidence from multiple studies suggests that GLP-1 has important cardiovascular actions, 12,14,15,38,39 the mechanisms underlying these diverse effects have not been fully elucidated. Our results propose a novel 2-pathway schema for cardiovascular actions of GLP-1, one that depends on the GLP-1R for inotropic action, glucose uptake, ischemic preconditioning, and mild vasodilatory actions and the second that depends on rapid metabolism of GLP-1 to GLP-1 , the latter having GLP-1R-independent effects on postischemic recovery of cardiac function and vasodilation.…”
Section: Discussionmentioning
confidence: 99%
“…GLP-1 co-administered with DPP-4 inhibitor, valine pyrrolide (VP), could reduce the infarct size ranging from 39% to 58% in isolated Langendorff rat hearts whether given prior to ischaemia or during the reperfusion period. [26][27][28][29] However, the administration of GLP-1 28 or DPP-4 inhibitor 26-28 alone failed to reduce the infarct size. These studies suggested the synergistic effect of DPP-4 inhibition and exogenous GLP-1 on the infarct limiting effect in which DDP-4 inhibitor enhanced endogenous GLP-1 level and reduced exogenous GLP-1 degradation.…”
Section: Effects Of Glp-1 On the Infarct Sizementioning
confidence: 99%
“…48,53 However, some studies demonstrated that prolonged availability of intact GLP-1 caused by a DPP-4 inhibitor failed to demonstrate the infarct limiting effect. [26][27][28]54 Moreover, inhibition or reduction of DPP-4 activity using DPP-4 deleted mice or pretreatment with sitagliptin before ischaemia in high fat diet-induced diabetic mice could not reduce the infarct size, but improved the survival rate by activation of cardioprotection kinase such as GSK3β, ANP and Akt. 49 These discrepant results suggest that the different animal models, the duration of ischaemia in the heart models and the minimal dose for a specific time may play a pivotal role in the reduction of the infarct size.…”
Section: Effects Of Dpp-4 Inhibitor On the Infarct Sizementioning
confidence: 99%
“…16 In addition to this chronotropic effect, a positive inotropic effect also has been attributed to direct myocardial activity. Recent evidence suggests that GLP-1 may enhance recovery of left ventricular function after transient coronary artery occlusion in an isolated rat heart model, 17,18 possibly mediated through insulin-like activity in improving glucose uptake by cardiomyocytes 17 and through the activation antiapoptotic signaling pathways shown to protect against myocardial injury. 19 A similar benefit has been demonstrated in conscious dogs with pacing-induced cardiomyopathy.…”
Section: Cardiovascular Impactmentioning
confidence: 99%